Key issues in crime and punishment - Chambliss, William J. (Thousand Oaks, Calif. : SAGE, 2011)
Topics in this title include such hotly debated topics as accountability, arrest practices, bounty hunters, entrapment, Miranda warnings, police privatization, profiling, vigilantes and sero-tolerance policing.
V. 1. Crime and criminal behavior -- v. 2. Police and law enforcement -- v. 3. Courts, law, and justice -- v. 4. Corrections -- v. 5. Juvenile crime and justice.
Includes bibliographical references and index.
Print version record.
Keywords: Crime; Law enforcement; Criminal justice, Administration of; Corrections; Lois -- Application; Services correctionnels; SOCIAL SCIENCE -- Criminology; Corrections; Crime; Criminal justice, Administration of